Nilai Pendidikan Karakter dalam Kekawin Bharatayuddha (Raja Salya Pralaya) - I Wayan Putu Yasa (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
One form of cultural variation that still exists today is Kekawin. Kekawin is an ancint Javanese literary work that still thriving during the Majapahit Kingdom. Kekawin has great values in it, so it can be used as a guide in living daily life by tha Balinese community. The purpose of the this research is to express and describe the Values of Character Education foud in the Kekawin of Bharatayuddha (Raja Salya Pralaya). These values are the value of hard work, the value of mutual cooperation, the value of national spirit, the value of independence, and the value of responsibility